Evidence for gas hydrate-filled fractures forming at the sulfate-methane transition zone, Hikurangi subduction margin, New Zealand - Brunet, Morgane; Cook, Ann; Martin, Saffron; Mountjoy, Joshu (Frontiers in Earth Science, 2025)
Using high-resolution X-ray computed tomography (X-CT) of sediment cores from International Ocean Discovery Program Expedition 372 offshore New Zealand, we identify a network of near-vertical, low-density structures interpreted as relics of gas hydrate-filled fractures. These fractures occur at shallow depths near the sulfate-methane transition zone (SMTZ), with widths (thickness) ranging from 0.5 to 5 mm and vertical extents between 7 and 60 mm. They are characterized by diffuse boundaries and steep dip angles. In contrast to previously documented hydrate-filled fractures, which are typically larger (centimeter to meter scale) and located deeper within the sediment column, these findings suggest that hydrate fracture formation can initiate at much shallower depths. We propose that these fractures represent early-stage hydrate formation; these fractures may increase in size over time as microbial methane production increases. The formation, dissociation or dissolution of hydrate-filled fractures may alter sediment structure, fluid migration pathways, and microbial community dynamics during early diagenesis. Moreover, the existence of shallow, fracture-hosted gas hydrate could facilitate rapid methane transport to the seafloor if dissociated, with significant implications for climate-sensitive environments such as the Arctic. Similar features identified in other settings support the hypothesis that shallow hydrate-filled fractures may be widespread but remain underreported due to limited X-CT imaging of shallow sediment intervals in scientific drilling. Expanding the application of high-resolution X-CT scanning, particularly across the SMTZ, is crucial to improve detection and understanding of near-seafloor hydrate systems and their potential environmental impacts.